Iron therapy and anthropometry: A case-control study among iron deficient preschool children - Amany Ibrahim; Abeer Atef; Rania Ismail Magdy; Mohammed Ali Farag (Egyptian Pediatric Association Gazette, 2017)
Background: Iron deficiency anemia (IDA) causes detrimental effects on physical growth which is attributed to poor appetite, altered endocrinologic profile and neurotransmitter metabolism. Objective: To investigate the iron status of preschool children with IDA and its association with the degree of growth retardation at presentation, and to detect the effect of iron supplementation on growth velocity (GV) over a period of one year. Materials and methods: A case-control study conducted in Diabetes Endocrine Metabolism Pediatric Unit in collaboration with the Pediatric Hematology clinic at Children’s Hospital, Cairo University included baseline and follow up anthropometric and hematological parameters of 40 IDA patients with mean age 2 ± 0.8 years compared to 40 healthy clinically non-anemic, age and sex-matched controls with mean age 2.7 ± 1.1 years. A daily total dose of 6 mg/kg/day of ferrous sulfate in 2–3 divided doses were given between meals to patients with IDA. Results: At presentation, patients with IDA had low hemoglobin, hematocrits, serum iron, serum ferritin, height standard deviation score (SDS), weight SDS, and body mass index (BMI) SDS which improved significantly after treatment. The GV of IDA patients correlated significantly with serum ferritin concentration and also their BMI SDS correlated significantly with the serum ferritin concentration. Conclusion: IDA during the first 6 years of life, when growth is fast, adversely affects both linear growth and weight gain which is reversible with iron therapy, thus adequate iron status is crucial for normal growth (height, weight and GV). The findings of the present study supported the beneficial effects of oral iron supplementation on physical growth parameters of IDA preschool children.